Humanized care in high-risk prenatal care: nurses' perceptions - Herla Maria Furtado Jorge; Raimunda Magalhães da Silva; Maria Yolanda Makuch (Universidade Federal do Ceará, 2020)
Objective: to unveil nurses' perceptions about humanized care in high-risk prenatal care. Methods: a qualitative study, with six nurses who worked in high-risk prenatal care. Data collection took place using semi-structured interviews. To analyze the results, the content analysis technique was used. Results: the adoption of humanized care consisted of actions related to user embracement, personalized care, dialogue with pregnant women and the establishment of a trustful relationship. The main humanization practices were guided visits to maternity hospitals; creating educational groups; the use of non-pharmacological methods for pain relief during labor; and encouraging companion support. Conclusion: participating nurses understood the humanization concept and associated humanization practices to the embracement of pregnant women, guided visits, personalized care, guidance on the use of non-pharmacological methods and the promotion of connections with pregnant women.